2015
DOI: 10.1007/s00404-015-3835-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, treatment and outcome of vaginal intraepithelial neoplasia

Abstract: VAIN has a high relapse rate and a high progression rate to invasive cancer especially if HR-HPV positive. Therefore, adequate follow-up examinations are mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 22 publications
6
37
5
Order By: Relevance
“…In the laser vaporisation group hrHPV persisted among 67% of the patients. Persistent hrHPV infection is a risk factor for recurrent disease . We did not detect differences in histological regression between imiquimod treatment or laser vaporisation.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…In the laser vaporisation group hrHPV persisted among 67% of the patients. Persistent hrHPV infection is a risk factor for recurrent disease . We did not detect differences in histological regression between imiquimod treatment or laser vaporisation.…”
Section: Discussioncontrasting
confidence: 68%
“…Multifocality of VAIN has been previously reported in 29–51% compared with 63% in our study . Our rate of hysterectomised patients (37%) was lower than in other studies (54–88%) …”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The vast majority (n = 19) of studies used formalin fixed paraffin embedded tissue for HPV DNA and/or p16 testing. Five studies reported using tissue samples, but did not specify tissue storage (i.e., fresh, frozen, or fixed) . In five studies, HPV DNA was extracted from exfoliated cells, and in one study, the type of material used was not reported .…”
Section: Resultsmentioning
confidence: 99%